Acoustic signatures, sound producing mechanisms and diversity of syngnathid fishes in Malaysian waters / Adam Lim Chee Ooi - Adam Lim, Chee Ooi (2017)
Syngnathid fishes are known to produce sounds in various behavioural contexts. While there are very few bioacoustic studies on seahorses, pipefishes have received even less attention. Such studies are sporadic, and there are no comparative studies within the family. This PhD study reveals that the feeding click of syngnathids is composed of multiple acoustic components (high and low frequency components) whereas the distress growl of the seahorse is of a solitary low-frequency component. Another low frequency sinusoidal component named as the purr is compounded with the feeding click. The acoustic parameters (frequency and time) of syngnathid feeding click and seahorse distress growl were found to be species-specific signatures with no statistical differences among individuals of the same species. The feeding click sound is produced by two dorsal cranial bones (posteriorly, the supraoccipital bone and coronet) which is consistent throughout the Hippocampus genus whereas pipefishes depict varied sound producing mechanisms. In the pipefish and pipehorse, these mechanisms consist of either three cranial bones (posteriorly, the supraoccipital, 1st postcranial plate and 2nd postcranial plate) as in Doryichthys spp., Trachythamphus serratus, Corythoichthys haematopterus, and Dunckerocampus dactyliophorus, or two bones (posteriorly, the supraoccipital and 2nd postcranial plate) in the absence of the 1st postcranial plate as in Syngnathoides biaculeatus, or presence of a vestigial 1st postcranial plate as in Acentronura tentaculata. The click sound components of the seahorse can be traced to the sliding movement and forceful contact between the supraorbital bone and coronet bone (=1st postcranial plate). In Doryichthyes pipefishes, the click sound components are generated when the supraoccipital slides backwards, striking and pushing the 1st postcranial plate against (and striking) the 2nd postcranial plate, whereas in Syngnathoides pipefish, the supraoccipital rubs against the 2nd postcranial plate. Both growl and purr have the same low frequency sound but are triggered under different conditions. The growl is accompanied by intense vibration at the cheek indicating another sound producing mechanism involving possibly the pectoral girdle. The purr is hypothesised to be a result of the coronet and supraocciptal bone strike that carries the signal to the pectoral girdle through stochastic resonance. The cranial morphology and kinesis of the examined syngnathids produced acoustic signals consistent with the bone strikes that produce sharp energy spikes, or stridulation between bones that produce repeated or multimodal sinusoidal waveforms. It is hypothesized here that the extant syngnathid species either retain the ancestral three-bone mechanism or possess a derived or modified form of this model. The production of species-specific acoustic parameters in seahorses is attributed to the individual shapes and size of the coronet bone despite a common modified two-bone mechanism throughout the Hippocampus genus. The different mechanisms in pipefishes (i.e. either three or two participating bones) promote variability in signal acoustic shape and parameters. The variation in cranial bone morphology, cranial kinesis and acoustic signatures among syngnathid fishes reflects the adaptive evolution within the Syngnathidae which may not be influenced by its habitat preferences.